1999
DOI: 10.1093/chemse/24.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Odor Identification, Consistency of Label Use, Olfactory Threshold and their Relationships to Odor Memory over the Human Lifespan

Abstract: The purpose of this study was to investigate olfactory threshold, odor identification, consistency of label use and their relationships to odor memory in the context of semantic/episodic memory across the human lifespan. A total of 137 subjects aged 4-90 years were tested with several olfactory test procedures. We found that olfactory sensitivity was well developed in children despite the finding that their odor naming and odor memory were inferior to that of adults. In the elderly population, olfactory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 63 publications
13
95
2
3
Order By: Relevance
“…Other researchers have tried to explain differences between cultures in terms of olfactory ability and odor preferences. However, learning may also play an important role in olfactory performance (Alaoui-Ismaïli, VernetMaury, Dittmar, Delhomme, & Chanel, 1997;Engen, 1988;Lehrner, Glück, & Laska, 1999).…”
Section: Universidad Nacional De Educación a Distancia Madrid Spainmentioning
confidence: 99%
“…Other researchers have tried to explain differences between cultures in terms of olfactory ability and odor preferences. However, learning may also play an important role in olfactory performance (Alaoui-Ismaïli, VernetMaury, Dittmar, Delhomme, & Chanel, 1997;Engen, 1988;Lehrner, Glück, & Laska, 1999).…”
Section: Universidad Nacional De Educación a Distancia Madrid Spainmentioning
confidence: 99%
“…Cain et al 7 reported that the sensitivity of children (aged 8-14y) was equivalent to that of young adults (aged 18-24y). Similarly, Lehrner et al 8 observed comparable results for butanol thresholds of children (aged 4-11y) and young adults (aged 18-30y). However, there is also research suggesting that children aged 5 to 9 years are less successful in an odour discrimination task than older children.…”
Section: Discussionmentioning
confidence: 66%
“…Likewise, both odor identification and odor recognition are negatively affected by aging (Larsson, 1997;Larsson & Bäckman, 1993;Larsson et al, 2004;Lehrner et al, 1999;Murphy et al, 1991;Ship & Weiffenbach, 1993). A vast majority of findings report of age-related impairments in odor identification ability (Doty et al, 1984;Dulay et al, 2008;Larsson et al, 2000).…”
Section: Olfactory Function In Normal Agingmentioning
confidence: 99%
“…However, other work did not find an interaction between sex and age in either odor identification or odor detection . Lehrner et al, (1999) reported that elderly subjects exhibited a detection impairment and that the detection thresholds were correlated with episodic odor memory, suggesting that a primary sensory impairment may be responsible for the odor recognition impairment observed in old age. Also, older subjects were impaired in remembering odors that had been identified correctly in an earlier task.…”
Section: Olfactory Function In Normal Agingmentioning
confidence: 99%